Formation of highly porous NiCo2S4 discs with enhanced pseudocapacitive properties through sequential ion-exchange. (5th May 2018) - Yu, Xing; Wang, Mengyi; Gagnoud, Annie; Fautrelle, Yves; Ren, Zhongming; Li, Xi
Highlights: The highly porous thin NiCo2 S4 discs are fabricated by sequential topotactic ion-exchange. Sequential ion-exchange can lead to sequential increase of specific surface area and porosity. The NiCo2 S4 electrode displays a high specific capacitance of 908 F g −1 at 3 A g −1 . The capacitance retention of the NiCo2 S4 electrode is 82% after 5000 cycles. The hybrid supercapacitor exhibits a high energy density of 42.7 Wh kg −1 at a power density of 375 W kg −1 . Graphical abstract: Unlabelled Image Abstract: In this work, we have developed a sequential chemically topotactic transformation strategy to fabricate highly porous thin NiCo2 S4 discs with complex crisscross pore channels through sequential in situ ion-exchange. Starting from Co3 O4 discs prepared by direct pyrolysis of solid Co-glycolate discs, complex porous Co3 S4 and NiCo2 S4 discs are obtained after the sequential ion-exchange reactions with S 2− and Ni 2+ ions, respectively. Physicochemical and electrochemical investigations demonstrate that the as-derived NiCo2 S4 discs with high electrical conductivity, ion-diffusion-derived large accessible surface area and pore volume present attractive pseudocapacitive properties including remarkably high capacitivity (908 F g −1 at 3 A g −1 ), good rate capability (610 F g −1 at 20 A g −1 ) and outstanding electrochemical stability with a capacitance retention of 82% after continuous cycling for 5000 cycles. Furthermore, a hybrid device using the NiCo2 S4 discs and carbon-based composite as positive and negative electrodes, respectively, delivers a high energy density of 42.7 Wh kg −1 at a power density of 375 W kg −1, suggesting that the NiCo2 S4 discs could be a powerful electrode platform for advanced supercapacitors.